(untitled) (Research, Society and Development, 2021)
It is important to know the nutritional composition of the fish, especially the nutritional value of the commercial cuts most consumed by the population. The aimed of this study was to evaluate the chemical composition of commercial tambaqui (Colossoma macropomum) cuts in different classes of body weight. The sample collections were carried out in processing units in two municipalities in the state of Rondônia, Brazil. The Data on 200 fish were recorded, with weight ranging from 1000 to 4700 g. Five classes of body weight were established, class 1 - below 1.2 kg; class 2 - from 1.21 to 1.8 kg; class 3 - from 1.81 to 2.4 kg; class 4 - from 2.41 to 3.5 kg; class 5 - over 3.5kg. The commercial cuts were lyophilized and intended for chemical analysis. The Kruskal-Wallis test (α=0.05) was used to compare the averages. The composition of commercial cuts was different in weight classes (p<0.05). The filet presented more representative values in mineral matter, crude protein and total lipids and lower humidity for class 4 (from 2.41 to 3.5 kg). The classes 1 and 5 (below 1.2 and over 3.5 kg) were different (p<0.05) in relation to the lipid and moisture content in the commercial filet and rib cuts. The tambaqui steak in class 4 have a higher lipid content compared to the average of the lightest body weight classes, 9.99 vs 4.50%, in addition to having a lower moisture content (p<0.05). The tambaqui band was different (p<0.05) in relation to nutritional components between body weight classes, with class 4 being richer in minerals, crude protein and lipids in dry matter. Therefore, the class 4 was the most efficient (p<0.05) for production and commercialization. Because the tambaquis with body weight between 2.4 to 3.5 kg stood out in relation to the nutritional components in the different commercial cuts.